A Multidisciplinary Framework of Information Propagation Online - Paletz, Susannah B. F.; Auxier, Brooke E.; Golonka, Ewa M. (SpringerBriefs in Complexity,, 2019)
This book presents a broad, multidisciplinary review of the factors that have been shown to or might influence sharing information on social media, regardless of its veracity. Drawing on literature from psychology, sociology, political science, communication, and information studies, the book provides a high-level framework of information sharing. The framework progresses through different categories. Information is first acquired or viewed from different sources; then, the target sharer has emotional and cognitive reactions to that information. The next categories involve motivations to share and the actual ability and perceptions of that ability to share. The greater context, such as culture, language, and social networks, also influences information sharing. Finally, the book distinguishes between genuine and non-genuine (inauthentic) actors. This text will appeal to students and especially to technical researchers looking for a social science perspective.